(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
The country relies on higher education because it helps create a knowledge-based society in the 21st Century. According to a report, 95% of Indian millennials aged between 18 and 34 said they are stressed, compared to the worldwide average of 86% (Cigna TTK Health Insurance Company report published in 2018). This research looked into main stress factors among university faculty and compared the results for both public and private university educators from Haryana. The research involved 187 public and 200 private sector educators, selected using purposive sampling. According to the analysis of data, the major sources of stress for educators are related to distance between required and preferred roles, role stagnation, role itself and ambiguity in roles. No real difference in role-stress was observed when considering gender. The stress from having many responsibilities was reported by educators from both types of schools. Furthermore, inter-role distance was found to be a big issue for private university teachers, but just a moderate issue for public school teachers, while role isolation ranked differently for both groups—in fact, none of the remaining dimensions came up as harmful stressors.